Pengaruh Model Pembelajaran PBL terhadap Hasil Belajar Keterampilan Passing Bawah Bola Voli - Binti Firda Aura; Mochamad Ridwan (MAN Insan Cendekia Jambi, 2026)
Volleyball teaching, particularly the underhand passing technique, still faces challenges due to low student engagement in conventional instruction. This study was conducted to determine the effect of implementing the Problem-Based Learning (PBL) model on improving learning outcomes in the underhand passing technique in volleyball. A quantitative approach was used, employing a quasi-experimental method and a nonequivalent control group design. The research subjects consisted of eighth-grade students divided into two groups: the experimental group and the control group. The experimental group received instruction using the PBL model, while the control group received conventional instruction. Descriptive statistics, tests to identify differences, and learning outcome assessments were used in the data analysis process. The results showed that the average score of the PBL group increased from 7.30 to 16.27, while that of the conventional group increased from 7.37 to 8.73. Statistical tests revealed a significant difference (p-value 0.000 < 0.05), with the PBL group’s N-Gain value at 76.836% (high) and the conventional group’s at 12.000% (low). Based on these findings, the PBL learning model can be considered a more effective method for improving learning outcomes in underhand passing in volleyball compared to conventional learning.